Intensity-modulated radiation therapy (IMRT) versus 3-dimensional conformal radiation therapy (3D-CRT) for head and neck cancer: cost-effectiveness analysis - Marta,Gustavo Nader (2018)
SUMMARY BACKGROUND: A cost-effectiveness analysis of IMRT compared to 3D-CRT for head and neck cancer patients (HNCPs) was conducted in the Brazilian Public Health System. METHODS: A Markov model was used to simulate radiation therapy-induced dysphagia and xerostomia in HNCPs. Data from the PARSPORT trial and the quality-of-life study were used as parameters. The incremental cost-effectiveness ratio (ICER) and cost per quality-adjusted life-year (QALY) gained were calculated. RESULTS: At 2 years, IMRT was associated with an incremental benefit of 0.16 QALYs gained per person, resulting in an ICER of BRL 31,579 per QALY gained. IMRT was considered cost-effective when using the guideline proposed by the World Health Organization (WHO) of three times the national gross domestic product (GDP) per capita (BRL 72,195). Regarding life expectancy (15 years), the incremental benefit of IMRT was 1.16 QALYs gained per person, with an ICER of BRL 4,341. IMRT was also cost-effective using the WHO definition, which states that the maximum cost is equal to the GDP per capita (BRL 24,065). CONCLUSIONS: IMRT was considered cost-effective from the perspective of the Brazilian public health system.